Empowering climate resilience: A people-centered exploration of Thailand's greenhouse gas emissions trading and sustainable environmental development through climate risk management in community forests - Chitralada Chaiya (Heliyon)
The imperative of addressing climate change has accentuated the pivotal role of reducing greenhouse gas emissions and harnessing the potential of community forests. This study meticulously explores the governance structures and mechanisms underpinning greenhouse gas emissions trading within community forests, aimed at curbing carbon emissions, and enhancing adaptive capacities in Thailand. With a central focus on cultivating enduring climate resilience, this research delves into the interplay of community perspectives with greenhouse gas emissions trading mechanisms, while also dissecting the genesis of sustainable strategies in the Thai context. Additionally, it rigorously assesses the determinants shaping community resilience and their responses to climatic fluctuations, contextualized within the framework of greenhouse gas emissions trading mechanisms. Employing a quantitative approach, data was gathered from 383 participants through a semi-structured questionnaire and analyzed using statistical techniques including paired t-tests, ANOVA, and multiple regressions. The study underscores the profound significance of each facet of carbon emissions reduction in relation to the Sustainable Development Goals (SDGs), with personal norms emerging as a potent driver in carbon trading. By unraveling these intricacies, the findings enrich our comprehension of the pivotal role community forests play in nurturing sustainable climate resilience, offering invaluable insights for policymakers, researchers, and practitioners to shape effective strategies for carbon mitigation and adaptive action.